Breast cancer surgery in older women: outcomes of the Bridging Age Gap in Breast Cancer study. Issue 11 (2nd June 2020) - Morgan, J L; George, J; Holmes, G; Martin, C; Reed, M W R; Ward, S; Walters, S J; Cheung, K Leung; Audisio, R A; Wyld, L
Abstract: Background: Breast cancer surgery in older women is variable and sometimes non-standard owing to concerns about morbidity. Bridging the Age Gap in Breast Cancer is a prospective multicentre cohort study aiming to determine factors influencing treatment selection and outcomes from surgery for older patients with breast cancer. Methods: Women aged at least 70 years with operable breast cancer were recruited from 57 UK breast units between 2013 and 2018. Associations between patient and tumour characteristics and type of surgery in the breast and axilla were evaluated using univariable and multivariable analyses. Oncological outcomes, adverse events and quality-of-life (QoL) outcomes were monitored for 2 years. Results: Among 3375 women recruited, surgery was performed in 2816 patients, of whom 24 with inadequate data were excluded. Sixty-two women had bilateral tumours, giving a total of 2854 surgical events. Median age was 76 (range 70–95) years. Breast surgery comprised mastectomy in 1138 and breast-conserving surgery in 1716 procedures. Axillary surgery comprised axillary lymph node dissection in 575 and sentinel node biopsy in 2203; 76 had no axillary surgery. Age, frailty, dementia and co-morbidities were predictors of mastectomy (multivariable odds ratio (OR) for age 1·06, 95 per cent c.i. 1·05 to 1·08). Age, frailty and co-morbidity were significant predictors of no axillary surgery (OR for age 0·91, 0·87 to 0·96). The rate of adverse events was moderate (551 of 2854, 19·3 per cent), with no 30-day mortality. Long-term QoL and functional independence were adversely affected by surgery. Conclusion: Breast cancer surgery is safe in women aged 70 years or more, with serious adverse events being rare and no mortality. Age, ill health and frailty all influence surgical decision-making. Surgery has a negative impact on QoL and independence, which must be considered when counselling patients about choices. Graphical Abstract: Age, ill health and frailty all influence surgical decision-making for breast cancer. Breast cancer surgery is safe, with serious adverse events being rare and no mortality. However, surgery has a negative impact on quality of life and independence, which must be considered when counselling patients about choices. Age defines treatment